Sistem Penunjang Keputusan Pemilihan Ketua UKM Bodhivijja dengan Menggunakan Metode Simple Additive Weighting (SAW) (Studi Kasus: STMIK Kharisma Makassar) - Marlina (JTRISTE, 2016)
Decision Support System in this study is in use by using simple additive weighting (SAW) is applied to the election of the chairman of the SME Bodhivijja , which is a student organization. SAW application of this by using five criteria: spirited leader , responsible , creative and innovative , honest and fair and have a good akedemik value . Defined 5 candidates for the chairman to be selected , and is calculated based on the SAW method . The results obtained by a chairman who has the highest score .